2020
DOI: 10.1136/bjsports-2019-101772
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sports injuries and later-life health status in 3357 retired Olympians from 131 countries: a cross-sectional survey among those competing in the games between London 1948 and PyeongChang 2018

Abstract: ObjectiveDescribe the self-reported prevalence and nature of Olympic-career injury and general health and current residual symptoms in a self-selected sample of retired Olympians.Methods3357 retired Olympians from 131 countries completed a cross-sectional online survey, distributed by direct email through World Olympians Association and National Olympian Associations databases. The survey captured Olympic sport exposure, significant training and competition injury history (lasting >1 month), general health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 58 publications
4
72
2
Order By: Relevance
“…The most prominent injury locations in retired GB Olympians were the knee, lumbar spine, and shoulder. These findings accord with data from retired athletes [ 26 ], and current athletes at the 2010 Winter Olympic Games in Vancouver [ 4 ]. In comparison, the thigh, knee, and lumbar spine were the most prominent injury locations at the Sochi 2014 Winter Olympic Games [ 27 ], compared to the knee, thigh, and ankle at the Rio de Janeiro 2016 Olympic Summer Games [ 9 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most prominent injury locations in retired GB Olympians were the knee, lumbar spine, and shoulder. These findings accord with data from retired athletes [ 26 ], and current athletes at the 2010 Winter Olympic Games in Vancouver [ 4 ]. In comparison, the thigh, knee, and lumbar spine were the most prominent injury locations at the Sochi 2014 Winter Olympic Games [ 27 ], compared to the knee, thigh, and ankle at the Rio de Janeiro 2016 Olympic Summer Games [ 9 ].…”
Section: Discussionsupporting
confidence: 87%
“…There is a paucity of existing data for whole career injuries in Olympians, with only one global study available that was conducted as a follow-up to the current study. Using a similar injury definition, the Retired Olympian Musculoskeletal Health Study (ROMHS) reported Olympic career sports injuries in 3357 former Olympians and found a 63.0% injury prevalence [ 26 ], compared to 56.6% in the present study. This lower injury prevalence in retired GB Olympians may in part reflect a higher injury prevalence among Winter Olympians in the ROMHS cohort and a reduced risk of exposure to injury in GB Olympians due to fewer years of participating within Olympic sports (mean 9.8 ± 6.2 years), compared to the ROMHS (mean 10.4 ± 5.6 years).…”
Section: Discussionmentioning
confidence: 70%
“…Elite sport participation can lead to an increased risk of injury, with injuries to the knee, lumbar spine, shoulder and ankle reported to be most frequent and also among the most severe in Olympic athletes 1–4. Even after acute symptoms have resolved athletes frequently report ongoing pain and dysfunction for years after an initial injury 4…”
Section: Introductionmentioning
confidence: 99%
“…Injury history was obtained from a questionnaire modified from the World Olympic Association Musculoskeletal Health Global Questionnaire 26 with three main components:…”
Section: Methodsmentioning
confidence: 99%